Oxidative stress assessment in intestine of newborn rats submitted to hypoxia and reoxygenation with tadalafil - Teixeira,Luciana Cristina (2019)
Abstract Purpose: To evaluate the functional and structural response of tadalafil effects in the intestinal mucosa, using an experimental model of hypoxia and reoxygenation injury in rats. Methods: The animals were divided into 4 groups: CTL, H/R, H/R+Td and M+Td. The newborn rats allocated in groups H/R, H/R+Td and M+Td were submitted twice a day, to a gas chamber with CO2 at 100% for 10 minutes and afterward reoxygenation with O2 at 98% for 10 minutes, in the three first days of life. Tadalafil dose was given to newborn of group H/R+Td and to the pregnant rat of group M+Td. Histological analysis was made with hematoxylin-eosin technique and oxidative stress through nitrite and nitrate levels and lipid peroxidation. Results: The histological analysis showed a reduction of mucosa alterations in the groups that received tadalafil. In the oxidative stress evaluation, occurred an increase of NO levels and less lipidic peroxidation in the ileum segments that received tadalafil. Conclusion: Tadalafil provides tissue protection when administered independently to both, pregnant or newborns.